Foam Agent Synthesis For the Production of Foam-Based Concrete - Izarul Machdar; Abdullah Abdullah; Adisalamun Adisalamun; Wahyu Rinadi (Journal of Applied Technology, 2023)
Foam agents are crucial in the durability and performance of foam-based concrete. This study provides a critical finding related to foam agent characteristics, foam decay, the effects of foam modifiers (NaCl), and the properties of foam concrete, including shrinkage, compressive strength, and density. The foaming agent was prepared using sodium dodecyl sulfate (SDS) and triethanolamine (TEA) as a surface active agent, propylene glycol (PG) as a solvent, and NaCl as the foam modifier. The SDS:TEA:PG ratio was 1:1:2. The foam modifier was introduced in 0.1% to 0.8% varying concentrations to assess its impact on foam stability. The surface tension of the foam agent synthesis at a concentration of 20% was measured to be 0.1649 N/m, comparable to the commercial one. The decay rate foam of 0.095, 0.059, 0.063, and 0.013 cm/minute for the concentrations of 20%, 40%, 60%, and 80%, respectively. This suggests that higher concentrations of the foaming agent resulted in a more stable foam structure with slower decay rates. Moreover, the results showed that as the NaCl increased, the viscosity increased, but no effect on foam concentration of 80%. It was also observed that the combined effect of the foam agent concentration and NaCl concentration on viscosity was not linear. The recorded foam concrete shrinkage heights for the 20%, 40%, and commercial foam agent concentrations were 6.45 mm (SD 1.07 mm), 5.04 mm (SD 0.62 mm), and 4.0 mm (SD 0.94 mm), respectively. Furthermore, the compressive strengths of the foam concrete for the 20%, 40% foam agent concentration, and commercial foam were 4.41 MPa (SD 0,79 MPa), 4.20 MPa (SD 0.48 MPa), and 6.32 MPa, respectively. In conclusion, the foaming agent formulated from the mixture of components SDS, TEA, PG, dan NaCl has demonstrated the ability to produce foam concrete with satisfactory quality.